Chemokine family significance and prognostic value in colorectal cancer - Ding, Yi; Chen, Yinnan; Xie, Siyun; Qiu, Quanpeng; Guo, Xiaolong; Feng, Yun; Li, Hongxia; Zhu, Fang; Liu, Yaping (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) poses a substantial global health concern, exhibits inconspicuous early symptoms, and is typically diagnosed at advanced stages leading to unfavorable outcomes. The intricate tumor microenvironment plays a crucial role in CRC development and progression, where chemokines contribute significantly. These chemokines exhibit widespread expression within tumor cells, facilitating immune cell infiltration, angiogenesis, and the establishment of distant metastases. The dysregulation of various chemokines in the context of CRC has emerged as a pivotal factor in the disease's pathogenesis.MethodsTo explore the relationship between chemokine gene expression and CRC patient survival, as well as to clarify their biological roles,We conducted RNA-sequencing (RNA-seq) analysis on a cohort of 88 CRC patients with tumor samples, thereby enabling a detailed exploration of chemokine involvement in CRC. This study was rigorously augmented using comprehensive datasets from The Cancer Genome Atlas (TCGA), ensuring a robust analysis of gene expression patterns associated with clinical outcomes.ResultsThrough data analysis, we identified key genes from the chemokine family thought pertinent to CRC outcomes. Consequently, we constructed a novel prognostic model based on the risk score derived from these chemokine expressions. Validation against clinical metadata, executed through immunohistochemistry analysis, affirmed the relevance and accuracy of our model in predicting patient survival.ConclusionOur findings illuminate the critical role of chemokines in shaping the immune microenvironment of CRC, thereby highlighting potential therapeutic targets for future treatment strategies. Our new prognostic model could provide important information for the development of targeted therapies for CRC, enhancing personalized treatment approaches andultimately improving survival for CRC patients.